Generation and evaluation of pharmacologically relevant drug-drug cocrystal for gout therapy - Modani, Sheela; Gunnam, Anilkumar; Yadav, Balvant; Nangia, Ashwini K.; Shastri, Nalini R. (Crystal Growth & Design, 2020)
The present study reports a novel drug-drug cocrystal of febuxostat and piroxicam for the treatment of gout. Single crystal X-ray diffraction revealed a monoclinic system with P2(1)/c space group. The prepared cocrystal enhanced the solubility of febuxostat and piroxicam and improved the dissolution rate of piroxicam in pH 6.8 as compared to the pure drug. Further, the compressibility assessment of cocrystal by Aulton and Wells method confirmed its plastic behavior and suitability for direct compression.